Decoloniality in the Grassroots and The Re-emergence of the Black Organic Intellectual - Clennon, Ornette D.; Sampaio, Claudia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book explores the relationship between "the roles of the Black "organic intellectual" and the PoC academic scholar, and outlines how important partnerships are emerging from these sometimes-contrasting decolonial praxes. By blending the decolonial processes of Indigenous rights via a liberation Psychology lens, Brazilian critical race scholarship and UK African diasporic collective consciousness via intersectional critical race studies, the authors provide a clear theoretical framework to show how a decolonised multi-layered community epistemology can be produced by the community for the community that in praxis form, can be employed for the fight for social justice within those communities. Ornette D Clennon is Visiting Professor, UFAM (Federal University of the Amazon) and Director of Research, MaCTRI (MEaP Academy Community Training & Research Institute), Manchester, UK. Claudia Regina Brandão Sampaio is Associate Professor, UFAM (Federal University of the Amazon), Coordinator of LABINS - Laboratory for Social Intervention and Community Development, Faculty of Psychology (FAPSI/UFAM), Brazil. .
Chapter 1 - From Manchester to Manaus, A Direct Connection -- Chapter 2 - The Discourses around Decoloniality in the UK and Brazil -- Chapter 3 - Scholar-activism and its Restrictions within the Academy in the UK -- Chapter 4 - Decolonial Praxis and Indigenous Social Justice in Brazil Universities -- Chapter 5 - Combining Decolonial Praxes of Indigenous and African diaspora Social Justice: The Emergence of the Glocal Black "Organic Intellectual".
Keywords: Social justice; Social structure; Equality; Sociology; Race; Imperialism; Social Justice; Social Structure; Public Sociology; Race and Ethnicity Studies; Imperialism and Colonialism